Measuring quantum discord at the LHC - Tao Han; Matthew Low; Navin McGinnis; Shufang Su (Journal of High Energy Physics)
Abstract There has been an increasing interest in exploring quantities associated with quantum information at colliders. We perform a detailed analysis describing how to measure the quantum discord in the top anti-top quantum state at the Large Hadron Collider (LHC). While for pure states, quantum discord, entanglement, and Bell nonlocality all probe the same correlations, for mixed states they probe different aspects of quantum correlations. The quantum discord, in particular, is interesting because it aims to encapsulate all correlations between systems that cannot have a classical origin. We employ two complementary approaches for the study of the top anti-top system, namely the decay method and the kinematic method. We highlight subtleties associated with measuring discord for reconstructed quantum states at colliders. Usually quantum discord is difficult to compute due to an extremization that must be performed. We show, however, that for the t t ¯ $$ t\overline{t} $$ system this extremization can be performed analytically and we provide closed-form formulas for the quantum discord. We demonstrate that with current LHC datasets, quantum discord can be observed at 3.6 – 5.7σ, depending on the signal region, with the decay method and can be measured at a precision of 0.1 – 0.2% with the kinematic method. At the high luminosity LHC, the observation of quantum discord is expected to be > 5σ using both the decay and kinematic methods and can be measured with a precision of 5% with the decay method and 0.05% with the kinematic method. Additionally, we identify the kinematic cuts at the LHC to isolate the t t ¯ $$ t\overline{t} $$ state that is separable but has non-zero discord. By systematically investigating quantum discord for the first time through a detailed collider analysis, this work expands the toolkit for quantum information studies in particle physics and lays the groundwork for deeper insights into the quantum properties in high-energy collisions.